Evaluation of the Implementation of the First Year of Audit Standards (SA 701) Communicating Key Audit Matters (E-Jurnal Akuntansi, 2024)
Auditing Standards (SA) 701 in Indonesia are effective for the implementation of general audits of financial statements of listed entities for the period starting on January 1, 2022. In this regard, this research was conducted to evaluate the implementation of the first year of enactment of SA 701. The research was conducted at Public Accounting Firm (Firm) ABC, which is one of the Firm in Indonesia. The data in this research uses primary data and secondary data. Primary data was obtained through semi-structured interviews, while secondary data was in the form of audit policies and procedures from Firm ABC. The research results show that Firm ABC is able to implement SA 701 well even though its international affiliate does not provide an audit methodology. The obstacles faced by Firm ABC in implementing SA 701 are communication with those charged with governance (TCWG) and management regarding Key Audit Matters, as well as the formulation of paragraphs on Key Audit Matters in the auditor's report. Regarding the implementation of the audit, there were no significant changes to the audit process, considering that the overall audit process carried out was still the same.
Keywords: SA 701; Key Audit Matters; Auditor's Report